Ischemia - Reperfusion: A look from yeast mitochondria - Stella, Carlos Alberto (2011)
The apoptotic phenomena observed in tissues which are subdued to ischemia and then to technical therapeutics of perfusion keep causing serious problems in the patient´s clinical recovery. Then, they constitute a challenge to resolve. The objective of this work is to discuss the intracellular mechanisms that lead cells to apoptosis during the ischemia-reperfusion process, taking into consideration that these phenomena are observable in a simple microorganism as the yeast Saccharomyces cerevisiae. Yeast provide an alternative study system in which the effects of certain cytoprotective drugs can be evaluated. The results can then be extrapolated to other types of cells. Several works have focused on the role of mitochondria in the apoptotic processes of cellular necrosis. One of the main factors responsible for this process is the unregulated opening of the permeability barrier. The inner membrane thus allows the unrestricted passage of ions and the release of apoptotic mediators from the inner membrane space towards the cytosol. Also, there is an increase in the level of reactive oxygen species (ROS) and the uncoupling of oxidative phosphorylation, which lead to the reversal of ATP synthesis to ATP hydrolysis. The driving cause of this complex process is the opening of an non-specific pore located in the mitochondrial membrane, denominated mammalian permeability transition pore (mPTP), which is also expressed in yeast (yPTP). From the functional point of view, the yeast pore presents some of the characteristics observed in mammals, and is similar in the defensive response against the deleterious mechanisms caused by oxidative stress. An increasing body of evidence supports the concept that the pharmacological inhibition of the mPTP is an actual and promising strategy for the protection of tissues in ischemic situations in order to avoid the damage induced by perfusion.